A Development Adaptive Content Web – Base Instruction. On : Data Investigation on the Internet for High Vocational Certificate level - Sira, Niwat; Sakulthai, Chaiyan; Phunmanee, Natthapong (SciTech Research Journal, 2018)
The purposes of the research were to development adaptive content Web – base Instruction. on : Data investigation on the internet for high vocational certificate level, to Study the performance of adaptive web – base instruction, and to find the sample’s satisfaction in the lessons. The research methodology system approach of 4 steps : 1) Analysis, 2) Design, 3) Development, and 4) Implement. The samples of the research ware 34 high vocational certificate level at Maha Sarakham technical college. The research instruments were adaptive content web – base instruction, questionnaire for expert of research’s form techniques, and questionnaire for sample’s satisfaction. The statistics used for analysis and evaluation were means, and standard deviation. The research findings showed that 1) The development of adaptive content web–base instruction lesson consisted management systems that registration system, website management system, teaching management system, learning tracking system, data management system, and lesson presentation. 2) The result of performance evaluation by technical experts revealed that their opinion was at high level (= 4.49, S.D. = 0.52). and 3) Students were satisfactory to the lesson at high level (= 4.40, S.D.=0.53) .